Gas nitriding method of iron-nickel-chromium austenite high-elasticity alloy

By performing high-temperature aging treatment and gas nitriding treatment in iron-nickel-chromium austenite high-elastic alloy, combined with sand blowing treatment, the problem of slow diffusion speed of nitrogen atoms is solved, and the surface hardness and elongation are significantly improved. Meet the needs of high hardness and good ductility.

CN119433422APending Publication Date: 2025-02-14SICHUAN AEROSPACE FENGHUO SERVO CONTROL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411575481.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The iron-nickel-chromium austenite high-elastic alloy has a slow diffusion rate of nitrogen atoms during gas nitriding treatment, resulting in low gas nitriding efficiency and cannot meet the product requirements of some high hardness requirements.

Method used

After high-temperature aging treatment (750-830℃, 3-5 hours), gas nitriding treatment is carried out, including the heating section, the nitriding section, the diffusion section and the cooling section, and sand blowing treatment is carried out after the high-temperature aging treatment to remove oxidation. membrane to increase the diffusion rate of nitrogen atoms.

Benefits of technology

The thickness and surface hardness of the nitriding treatment layer are significantly improved, the hardness is increased to above 1050HV, and the elongation reaches more than 10%, meeting the needs of high hardness and good ductility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005121684850000061
    Figure BDA0005121684850000061
  • Figure BDA0005121684850000091
    Figure BDA0005121684850000091
  • Figure BDA0005121684850000092
    Figure BDA0005121684850000092
Patent Text Reader

Abstract

The invention provides a gas nitriding method of an iron-nickel-chromium austenite high-elasticity alloy. The method comprises the steps that the iron-nickel-chromium austenite high-elasticity alloy is subjected to high-temperature aging treatment, the temperature of the high-temperature aging treatment ranges from 750 DEG C to 830 DEG C, and the heat preservation time of the high-temperature aging treatment ranges from 3 h to 5 h; and the alloy subjected to high-temperature aging treatment is subjected to gas nitriding treatment. The aging temperature of the iron-nickel-chromium austenite high-elasticity alloy is increased to 750-830 DEG C, so that the hardness of the alloy is properly reduced, and the plasticity of the alloy is remarkably enhanced; the reduction of the hardness enables nitrogen atoms to enter more easily, so that the gas nitriding speed is accelerated, and finally the thickness and the surface hardness of a nitriding treatment layer are improved; and the plasticity is improved, so that the alloy has good ductility, and the ductility of the alloy reaches 10% or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a surface treatment method of an iron-nickel-chromium series austenitic high-elasticity alloy, in particular to a gas nitriding method of an iron-nickel-chromium series austenitic high-elasticity alloy. Background Art

[0002] Iron-nickel-chromium austenitic high elastic alloy (also known as 3J1 alloy) is a precision alloy formed by the fusion of multiple elements. It has excellent properties such as high elastic modulus, low elastic aftereffect, corrosion resistance, non-magnetic, and an operating temperature of up to 250°C. Therefore, it is widely used in the manufacture of precision elastic components and objects in aerospace, electronics, machinery, and instrumentation.

[0003] The most common heat treatment method for iron-nickel-chromium austenitic high elastic alloys is aging heat treatment, and the aging temperature is generally 500-650℃. Aging treatment at this temperature can improve the hardness of the material. However, after aging treatment, the surface hardness of iron-nickel-chromium austenitic high elastic alloys is usually only in the range of 300-400HV, which cannot meet the hardness requirements of some products with higher hardness requirements. Especially for some parts that require high-frequency conversion, the hardness of the alloy after aging treatment is not enough, resulting in poor wear resistance, easy to cause wear, and affect the precision of the product.

[0004] In order to improve its surface hardness, the iron-nickel-chromium austenitic high elastic alloy needs to be surface treated, such as gas nitriding. Gas nitriding is to place the iron-nickel-chromium austenitic high elastic alloy in ammonia gas, which decomposes at high temperature to produce active nitrogen atoms. The active nitrogen atoms penetrate into the metal matrix. These nitrogen atoms dissolve in γ-Fe and α-Fe to form Fe2-3N and Fe4N iron-nitrogen compounds. These iron-nitrogen compounds can greatly improve the surface hardness, wear resistance and corrosion resistance of the material, and obtain excellent surface properties.

[0005] Since the Fe-Ni-Cr austenitic high elastic alloy has a face-centered cubic structure, the diffusion rate of nitrogen atoms in austenite is slow during the gas nitriding process, resulting in poor gas nitriding efficiency. Currently, there is no process that can effectively solve this problem. Summary of the invention

[0006] The invention aims to solve the problem that the diffusion rate of nitrogen atoms is slow during the gas nitriding treatment of an iron-nickel-chromium austenitic high elastic alloy, resulting in low gas nitriding efficiency, and proposes a gas nitriding method for an iron-nickel-chromium austenitic high elastic alloy.

[0007] The technical method of the present invention is as follows:

[0008] A gas nitriding method for an iron-nickel-chromium austenitic high elastic alloy, the method comprising:

[0009] S1. subjecting the iron-nickel-chromium series austenitic high elastic alloy to high temperature aging treatment, wherein the temperature of the high temperature aging treatment is 750-830° C., and the holding time of the high temperature aging treatment is 3-5 hours;

[0010] S2. Performing gas nitriding treatment on the alloy after high temperature aging treatment.

[0011] In the present invention, after the step S1, a sand blasting process is also included.

[0012] Specifically, the sand blowing treatment is water-blowing sand treatment, the raw material of the water-blowing sand treatment is 50-150 mesh sand particles, the medium of the water-blowing sand treatment is water, the pressure of the water-blowing sand treatment is 0.2-0.4 MPa, and the coverage of the water-blowing sand is 150-200%.

[0013] In the present invention, the gas nitriding treatment step includes: placing the alloy after high-temperature aging treatment into a nitriding furnace, and sequentially performing a heating stage, a nitriding stage, a diffusion stage, and a cooling stage.

[0014] Specifically, the temperature rising step includes: introducing nitrogen into the nitriding furnace, exhausting the air in the furnace, and raising the temperature to 500-560° C. during the introduction of ammonia; wherein the heating rate is less than or equal to 90° C. / h.

[0015] Specifically, the nitriding stage includes: continuously introducing ammonia, controlling the temperature of the nitriding furnace at 500-560° C., the nitriding time at 30-50 hours, the decomposition rate of ammonia at 30-50%, and the pressure in the nitriding furnace at 0.1-0.3 MPa.

[0016] Specifically, the diffusion section includes: continuously introducing ammonia gas, controlling the temperature of the nitriding furnace at 530-580° C., keeping the temperature for 1-2 hours, and the decomposition rate of ammonia gas at 60-80%.

[0017] Specifically, the cooling stage includes: continuously introducing ammonia gas, controlling the temperature of the nitriding furnace to drop below 150°C, and then stopping the introduction of ammonia gas and cooling the furnace; wherein the cooling rate is less than or equal to 130°C / h.

[0018] The present invention adopts the above-mentioned gas nitriding method of the iron-nickel-chromium series austenitic high elastic alloy to obtain the gas nitrided iron-nickel-chromium series austenitic high elastic alloy.

[0019] Specifically, the surface hardness of the gas-nitrided iron-nickel-chromium austenitic high elastic alloy is above 1050 HV, the elongation is above 10%, and the thickness of the nitrided layer is above 25 um.

[0020] The beneficial effects of the present invention are:

[0021] 1. The present invention increases the aging temperature of the iron-nickel-chromium austenitic high elastic alloy to 750-830°C, which not only moderately reduces the hardness of the alloy, but also significantly enhances its plasticity; the reduction in hardness makes it easier for nitrogen atoms to enter, thereby accelerating the gas nitriding rate, and ultimately increasing the thickness and surface hardness of the nitriding treatment layer; the improvement in plasticity makes it have good ductility, and its elongation reaches more than 10%.

[0022] 2. Since an oxide film is easily formed on the surface of an iron-nickel-chromium austenitic high elastic alloy, which hinders the diffusion of nitrogen atoms into the steel, the present invention uses sand blasting to destroy the dense oxide film on the surface of the material and increase the surface defect density of the material, thereby increasing the gas nitriding rate and ultimately improving the thickness and surface hardness of the nitriding layer.

[0023] 3. The present invention uses samples after high-temperature aging for nitriding treatment, and the nitriding time is controlled at 30-50h. The thickness of the nitrided layer after the alloy nitriding treatment is 25-30um. The present invention performs nitriding treatment by increasing the aging temperature and performing sand blasting treatment. The nitriding time is controlled at 30-50h. The thickness of the nitrided layer after the alloy nitriding treatment can reach more than 35um.

[0024] 4. The present invention increases the aging temperature, performs sand blasting and gas nitriding, so that the surface hardness of the generated gas nitrided iron-nickel-chromium austenitic high elastic alloy is above 1050HV, the elongation is above 10%, and the thickness of the nitriding layer is above 25um. DETAILED DESCRIPTION

[0025] The technical solution of the present invention is described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] In the prior art, during the aging treatment of the iron-nickel-chromium austenitic high elastic alloy, its hardness first increases and then decreases with the increase of temperature, reaching a maximum value at 650°C. Therefore, researchers tend to perform aging treatment on the iron-nickel-chromium austenitic high elastic alloy at a temperature below 650°C to increase the hardness of the material, and then perform gas nitriding treatment to increase the hardness of the material. However, this method not only has slow diffusion of nitrogen atoms, but also has very poor elongation after nitriding, and the material is brittle and prone to brittle fracture.

[0027] The idea of ​​the present invention is to increase the aging temperature to 750-830°C, thereby reducing the hardness of the material and improving the plasticity. Due to the reduction in hardness, the interatomic gaps are increased, which is more conducive to the entry of nitrogen atoms, thereby increasing the gas nitriding rate and thus increasing the thickness of the nitriding layer. At the same time, the present invention also removes the oxide film on the surface of the material through sand blasting, preferably when blowing water sand, and at the same time increases the defect density of the material, thereby increasing the gas nitriding rate and ultimately increasing the thickness of the nitriding layer.

[0028] The present invention provides a gas nitriding method for an iron-nickel-chromium series austenitic high elastic alloy, the method comprising:

[0029] S1. Perform high temperature aging treatment on the iron-nickel-chromium series austenitic high elastic alloy.

[0030] Specifically, the iron-nickel-chromium series austenitic high elastic alloy is a cold-drawn bar material, which has a relatively high hardness and a relatively poor elongation.

[0031] Specifically, the composition of the iron-nickel-chromium austenitic high elastic alloy is: 0.01wt% C, 0.60wt% Si, 0.72wt% Mn, 0.012wt% P, 0.009wt% S, 36.1wt% Ni, 11.8wt% Cr, 3.02wt% Ti, and 1.13wt% Al.

[0032] Among them, the temperature of high temperature aging treatment is 750-830℃. For example, 760℃, 770℃, 790℃, 810℃. The holding time of high temperature aging treatment is 3-5h. For example, the time is 3.5h, 4h, 4.5h. During the aging treatment, when the temperature exceeds 650℃, the hardness of the material begins to decrease. However, in order to achieve the hardness range we specify, the aging temperature is usually set between 750 and 830℃. In addition, the specific aging temperature depends on the hardness of the material before nitriding. If the hardness of the material before nitriding is large, the aging temperature needs to be increased; conversely, if the hardness is low, the aging temperature should be appropriately reduced. In the embodiment, since the hardness of the iron-nickel-chromium austenitic high elastic alloy used is about 497HV, a higher 750-830℃ is selected as the aging temperature. Therefore, by keeping warm at 750-830℃ for 3-5h, the plasticity of the material can be improved and the hardness of the material can be appropriately reduced.

[0033] In one embodiment, the hardness of the alloy after high temperature aging treatment is about 300 HV, the elongation is about 16%, and the tensile strength is about 1000 MPa.

[0034] In one embodiment, step S1 further includes a sand blasting process.

[0035] In one embodiment, the sand blasting process can be water sand blasting or dry sand blasting. Among them, the dry sand blasting has larger particles, a rougher surface after the dry sand blasting, a higher dislocation density, and is more conducive to the entry of nitrogen atoms. However, the surface of the material after the dry sand blasting is too rough, and the processing is too difficult, so water sand blasting is the best choice.

[0036] Specifically, the raw material for water sand blowing treatment is 50-150 mesh sand, the medium for water sand blowing treatment is water, the pressure for water sand blowing treatment is 0.2-0.4 MPa, and the coverage rate of water sand blowing is 150-200%. Here, the 150-200% coverage rate adopted in the invention can achieve full coverage of the material and ensure the sand blowing effect. If the pressure value is greater than 0.4 MPa, the surface roughness will increase and affect the surface quality of the product. If the pressure value is lower than 0.2 MPa, the sand blowing effect will not be achieved.

[0037] In one embodiment, after step S1, cooling is further performed using an inert gas. The inert gas may be nitrogen, which is the most widely used due to its low cost and good cooling effect.

[0038] On the one hand, the sand blasting treatment of the present invention can arbitrarily select between different roughnesses, thereby achieving control of the surface quality of the iron-nickel-chromium series austenitic high elastic alloy, thereby achieving processing of products with high surface precision requirements. On the other hand, the oxide film on the surface of the material is removed by the sand blasting treatment, while increasing the defect density on the surface of the material, thereby increasing the gas nitriding rate.

[0039] S2. Performing gas nitriding treatment on the alloy after high temperature aging treatment.

[0040] In one embodiment, the step of gas nitriding treatment includes: placing the alloy after high temperature aging treatment into a nitriding furnace, and sequentially performing a heating stage, a nitriding stage, a diffusion stage, and a cooling stage.

[0041] Specifically, the heating stage step includes: introducing nitrogen into the nitriding furnace, exhausting the air in the furnace, and heating to 500-560°C during the introduction of ammonia. For example, heating to 510°C, 520°C, 530°C, 530°C, 550°C. Here, heating to 500-560°C is high-temperature nitriding, and high-temperature nitriding can obtain a deeper nitriding layer and a higher surface hardness. Among them, the heating rate is less than or equal to 90°C / h. The heating rate can be 70°C / h, 80°C / h. Here, a heating rate greater than 90°C / h will cause uneven temperature of the material and affect the nitriding effect.

[0042] Preferably, as the temperature of the nitriding furnace increases, the amount of ammonia introduced is increased to ensure that the ammonia decomposition rate in the subsequent nitriding furnace is controlled at 10-30% and the pressure is controlled at 0.05-0.15 MPa.

[0043] Specifically, the nitriding stage includes: continuously introducing ammonia, controlling the temperature of the nitriding furnace at 500-560°C, the nitriding time at 30-50h, the decomposition rate of ammonia at 30-50%, and the pressure in the nitriding furnace at 0.1-0.3MPa. For example, the temperature is 510°C, 520°C, 530°C, 530°C, 550°C. The time is 35h, 40h, 45h. The decomposition rate of ammonia is 35%, 40%, 45%. The pressure is 0.15MPa, 0.2MPa, 0.25MPa. The present invention controls the nitriding time at 30-50h. Since the greater the atomic concentration difference, the greater the diffusion flux, the easier it is for diffusion to occur, the higher the ammonia decomposition rate, the higher the surface nitrogen atom concentration, and the more conducive it is for nitrogen atoms to diffuse into the material.

[0044] Here, the decomposition rate of ammonia is greatly affected by pressure and temperature. Generally, the higher the temperature, the higher the ammonia decomposition rate and the faster the nitriding speed, but too high a decomposition rate may lead to reduced quality of the nitriding layer. The higher the pressure, the higher the ammonia decomposition rate, but too high a pressure may lead to equipment risks and energy waste. Therefore, the present invention controls the ammonia decomposition rate to 30-50% by adjusting the temperature of the nitriding furnace to 500-560°C and the pressure in the nitriding furnace to 0.1-0.3MPa.

[0045] Specifically, the diffusion stage step includes: continuously introducing ammonia, controlling the temperature of the nitriding furnace at 530-580°C, keeping the temperature for 1-2 hours, and the decomposition rate of ammonia at 60-80%. For example, the temperature is 540°C, 550°C, 560°C, 570°C. The time is 1.2 hours, 1.5 hours, 1.8 hours. Here, the purpose of the diffusion stage is to increase the diffusion rate of nitrogen atoms and increase the depth of the nitriding layer, and a 60-80% ammonia decomposition rate is required.

[0046] Preferably, the furnace temperature of the diffusion section is higher than the furnace temperature of the nitriding section, which promotes further diffusion of nitrogen atoms into the alloy after the sand blasting treatment and helps to form a deeper nitriding layer.

[0047] Specifically, the cooling stage includes: continuously introducing ammonia, controlling the temperature of the nitriding furnace to drop below 150°C, then stopping the introduction of ammonia, and cooling with the furnace. For example, the temperature drops to 140°C, 130°C, and 120°C. Here, the temperature of the nitriding furnace is controlled to drop below 150°C, and then the introduction of ammonia is stopped to ensure that the material will not be oxidized and discolored. If the introduction of ammonia is stopped during the cooling process, oxygen in the air will enter the furnace, causing the parts to be oxidized by air at high temperatures.

[0048] The cooling rate is less than or equal to 130°C / h. The cooling rate can be 120°C / h or 125°C / h. Here, the cooling rate can be appropriately increased compared to the heating rate, because such adjustment has little effect on the performance of the material. Under the condition of considering cost-effectiveness, the cooling rate can be appropriately increased.

[0049] The present invention also provides a gas nitrided iron-nickel-chromium austenitic high elastic alloy, which is obtained by the gas nitriding method of the iron-nickel-chromium austenitic high elastic alloy.

[0050] The surface hardness of the gas nitrided iron-nickel-chromium austenitic high elastic alloy is above 1050 HV, the elongation is above 10%, and the thickness of the nitrided layer is above 25 um.

[0051] The present invention will be further described in detail below with reference to specific embodiments.

[0052] Example 1

[0053] This embodiment provides a gas nitriding method for an iron-nickel-chromium series austenitic high elastic alloy, the method adopts high temperature aging treatment and gas nitriding treatment, and includes the following steps:

[0054] The composition of the test iron-nickel-chromium austenitic high elastic alloy is shown in the following table (wt%):

[0055]

[0056] The alloy is originally a cold-drawn bar with high hardness, but poor properties such as elongation.

[0057] (1) High temperature aging treatment: The iron-nickel-chromium austenitic high elastic alloy was aged at 810°C for 3.5 hours and cooled with nitrogen. The mechanical properties of the material after high temperature aging treatment were as follows: tensile strength 1029MPa, yield strength 683MPa, elongation 15.9%, and hardness 308HV.

[0058] (2) Gas nitriding treatment: After high-temperature aging treatment, the iron-nickel-chromium austenitic high elastic alloy is loaded into the nitriding furnace, and ammonia gas is introduced to exhaust the air in the furnace. After the air is exhausted, the temperature is increased at a rate of ≤90℃ / h to ensure that the temperature of the workpiece is the same as the furnace temperature. As the furnace temperature rises, the amount of ammonia introduced is increased to ensure that the ammonia decomposition rate in the furnace is controlled at 10-30%, and the pressure is controlled at 0.1-0.3MPa. After reaching the temperature, the nitriding treatment is started, the temperature is controlled at 515℃, the ammonia decomposition rate is 30-50%, the nitriding time is 30h, and the pressure in the furnace is maintained at 0.15MPa; after nitriding for 30h, the temperature is raised to 545℃, the ammonia decomposition rate is controlled at 65%, diffusion is carried out, and the insulation time is 1.5h. Then the temperature is lowered at a rate of ≤130℃ / h, and the gas is stopped when it drops below 150℃, and the furnace is cooled.

[0059] Performance testing: GX-51 microscope and FEM-8000 micro-measurement system were used to test the depth of nitrided layer and the depth of nitrided layer of the sample. After grinding off the 10um brittle layer on the surface, the hardness and brittleness of the nitrided layer were tested. The mechanical properties of the material were tested using a tensile testing machine. The test results showed that the depth of the nitrided layer was 26um. After grinding off the 10um brittle layer on the surface, the hardness of the nitrided layer was 1108HV, the brittleness of the nitrided layer was level 1, the tensile strength was 1096MPa, the yield strength was 687MPa, and the elongation was 13.2%; compared with the sample that was not nitrided after aging, the surface hardness increased from 308HV to 1096HV, and the hardness increased by 788HV.

[0060] Example 2

[0061] This embodiment provides a gas nitriding method for an iron-nickel-chromium series austenitic high elastic alloy, the method adopts high temperature aging treatment, sand blasting treatment and gas nitriding treatment, and includes the following steps:

[0062] (1) High temperature aging treatment: The iron-nickel-chromium austenitic high elastic alloy (consistent with the composition and state of the iron-nickel-chromium austenitic high elastic alloy in Example 1) was subjected to high temperature aging treatment at 810°C for 3.5 hours, and nitrogen was used for cooling. The mechanical properties of the material after high temperature aging treatment were as follows: tensile strength 1029 MPa, yield strength 683 MPa, elongation 15.9%, and hardness 308 HV.

[0063] (2) Sand blasting treatment: The iron-nickel-chromium austenitic high elastic alloy after high temperature aging treatment was subjected to water sand blasting treatment. The sand particle size used was 100 mesh, the sand blasting pressure was 0.3 MPa, the water sand blasting time was 3 min, and the sand particle coverage rate was 200%. After water sand blasting, the surface of the sample appeared silvery white. Here, the surface roughness was not much different from that before sand blasting, and the surface would not be too rough, thereby reducing the difficulty of processing and facilitating processing.

[0064] (3) Gas nitriding treatment: After the sandblasting treatment, the iron-nickel-chromium austenitic high elastic alloy is loaded into the nitriding furnace, and ammonia gas is introduced to exhaust the air in the furnace. After the air is exhausted, the temperature is increased at a rate of ≤90℃ / h to ensure that the temperature of the workpiece is the same as the furnace temperature. As the furnace temperature rises, the amount of ammonia introduced is increased to ensure that the ammonia decomposition rate in the furnace is controlled at 10-30%, and the pressure is controlled at 0.1-0.3MPa. After reaching the temperature, the nitriding treatment is started, the temperature is controlled at 515℃, the ammonia decomposition rate is 30-50%, the nitriding time is 30h, and the pressure in the furnace is maintained at 0.15MPa; after nitriding for 30h, the temperature is increased to 545℃, the ammonia decomposition rate is controlled at 65%, diffusion is carried out, and the insulation time is 1.5h. Then the temperature is lowered at a rate of ≤130℃ / h, and the gas is stopped below 150℃, and the furnace is cooled.

[0065] Performance testing: GX-51 microscope and FEM-8000 micro-measurement system were used to test the depth of nitrided layer and the depth of nitrided layer of the sample. After grinding off the 10um brittle layer on the surface, the hardness and brittleness of the nitrided layer were tested. The mechanical properties of the material were tested using a tensile testing machine. The test results showed that the depth of the nitrided layer was 40um. After grinding off the 10um brittle layer on the surface, the hardness of the nitrided layer was 1116HV, the brittleness of the nitrided layer was level 1, the tensile strength was 1150MPa, the yield strength was 690MPa, and the elongation was 12.1%; compared with the sample that was not nitrided after aging, the surface hardness increased from 308HV to 1116HV, and the hardness increased by 808HV.

[0066] Comparative Example 1

[0067] This embodiment provides a gas nitriding method for an iron-nickel-chromium austenitic high elastic alloy, which only uses gas nitriding treatment and includes the following steps:

[0068] (1) Mechanical properties of an iron-nickel-chromium austenitic high elastic alloy (consistent with the composition and state of the iron-nickel-chromium austenitic high elastic alloy in Example 1) were tested, and the experimental data obtained were: tensile strength of 1757 MPa, yield strength of 1302 MPa, elongation of 6.5%, and hardness of 497 HV.

[0069] (2) Nitriding treatment: directly load the iron-nickel-chromium austenitic high elastic alloy into the nitriding furnace, start to introduce ammonia, exhaust the air in the furnace, and after the air is exhausted, heat up at a rate of ≤90℃ / h to ensure that the temperature of the workpiece is the same as the furnace temperature. As the furnace temperature rises, increase the amount of ammonia introduced to ensure that the ammonia decomposition rate in the furnace is controlled at 10-30%, and the pressure is controlled at 0.1-0.3MPa. After reaching the temperature, start nitriding treatment, control the temperature to 515℃, the ammonia decomposition rate to 30-50%, the nitriding time to 30h, and keep the pressure in the furnace at 0.15MPa; after nitriding for 30h, heat up to 545℃, control the ammonia decomposition rate to 65%, diffuse, and keep warm for 1.5h; cool down: the cooling rate is ≤130℃ / h, stop the gas below 150℃, and cool with the furnace.

[0070] Performance testing: GX-51 microscope and FEM-8000 micro-measurement system were used to test the depth of nitrided layer and the depth of nitrided layer of the samples. After grinding off the 10um brittle layer on the surface, the hardness and brittleness of the nitrided layer were tested. The mechanical properties of the material were tested using a tensile testing machine. The test results showed that the depth of the nitrided layer was 20um. After grinding off the 10um brittle layer on the surface, the hardness of the nitrided layer was 1127HV, the brittleness of the nitrided layer was level 1, the tensile strength was 1832MPa, the yield strength was 1302MPa, and the elongation was 3.9%; compared with the sample that was not nitrided after aging, the surface hardness increased from 497HV to 1127HV, and the hardness increased by 630HV.

[0071] Comparative Example 2

[0072] A gas nitriding method for an iron-nickel-chromium series austenitic high elastic alloy, the method adopts sand blasting treatment and nitriding treatment, and comprises the following steps:

[0073] (1) Mechanical properties of an iron-nickel-chromium austenitic high elastic alloy (consistent with the composition and state of the iron-nickel-chromium austenitic high elastic alloy in Example 1) were tested, and the experimental data obtained were: tensile strength of 1757 MPa, yield strength of 1302 MPa, elongation of 6.5%, and hardness of 497 HV.

[0074] (2) Sand blasting treatment: The iron-nickel-chromium austenitic high elastic alloy is directly subjected to water sand blasting treatment. The sand particle size used is 100 mesh, the sand blasting pressure is 0.3 MPa, the water sand blasting time is 3 min, and the shot peening coverage rate is 200%. After water sand blasting, the surface of the sample appears silvery white, and the surface roughness is not much different from that before sand blasting.

[0075] (3) Nitriding treatment: After the sandblasting treatment, the iron-nickel-chromium austenitic high elastic alloy is loaded into the nitriding furnace, and ammonia gas is introduced to exhaust the air in the furnace. After the air is exhausted, the temperature is increased, and the heating rate is ≤90℃ / h to ensure that the workpiece temperature is the same as the furnace temperature. As the furnace temperature rises, the amount of ammonia introduced is increased to ensure that the ammonia decomposition rate in the furnace is controlled at 10-30%, and the pressure is controlled at 0.1-0.3MPa. After reaching the temperature, the nitriding treatment is started, and the temperature is controlled at 515℃, the ammonia decomposition rate is 30-50%, the nitriding time is 30h, and the pressure in the furnace is maintained at 0.15MPa; after nitriding for 30h, the temperature is increased to 545℃, the ammonia decomposition rate is controlled at 65%, and diffusion is carried out, and the insulation time is 1.5h. Cooling: The cooling rate is ≤130℃ / h, and the gas is stopped below 150℃, and the furnace is cooled.

[0076] Performance testing: GX-51 microscope and FEM-8000 micro-measurement system were used to test the depth of nitrided layer and the depth of nitrided layer of the sample. After grinding off the 10um brittle layer on the surface, the hardness and brittleness of the nitrided layer were tested. The mechanical properties of the material were tested using a tensile testing machine. The test results showed that the depth of the nitrided layer was 32um. After grinding off the 10um brittle layer on the surface, the hardness of the nitrided layer was 1143HV, the brittleness of the nitrided layer was level 1, the tensile strength was 1914MPa, the yield strength was 1315MPa, and the elongation was 3.5%; compared with the sample that was not nitrided after aging, the surface hardness increased from 497HV to 1143HV, and the hardness increased by 646HV.

[0077] Performance comparison

[0078]

[0079] Table 1 Comparison of Example 1 before and after nitriding treatment

[0080] As shown in Table 1, compared with the sample without nitriding treatment after aging, the surface hardness increased from 308 HV to 1096 HV, and the hardness increased by 788 HV.

[0081]

[0082] Table 2 Comparison of Example 2 before and after nitriding treatment

[0083] As shown in Table 2, compared with the sample without nitriding treatment after aging, the surface hardness increased from 308HV to 1116HV, and the hardness increased by 808HV.

[0084]

[0085] Table 3 Comparison of Comparative Example 1 before and after nitriding treatment

[0086] As shown in Table 3, compared with the sample without nitriding after aging, the surface hardness increased from 497 HV to 1127 HV, and the hardness increased by 630 HV. Here, the hardness increase rate is slower than that of Example 1 and Example 2, and the ductility is not good.

[0087]

[0088] Table 3 Comparison of Comparative Example 2 before and after nitriding treatment

[0089] As shown in Table 4, compared with the sample without nitriding after aging, the surface hardness increased from 497 HV to 1143 HV, and the hardness increased by 646 HV.

[0090]

[0091] Table 5

[0092] As shown in Table 5:

[0093] Compared with Comparative Example 1, due to the high-temperature aging treatment of the material, the depth of the nitriding layer of Example 1 is thicker than that of Comparative Example 1, that is, the nitriding efficiency of Example 1 is higher than that of Comparative Example 1. The elongation of Example 1 is much greater than that of Comparative Example 1. Although the present invention reduces the hardness of the material during high-temperature aging, the subsequent gas nitriding treatment can effectively increase the surface hardness of Example 1 to a level similar to that of Comparative Example 1, ensuring that the material achieves the required surface hardness while maintaining good elongation.

[0094] Compared with Example 2, Example 1 has a thicker nitrided layer because Example 2 is subjected to sand blasting treatment, which indicates that the nitriding efficiency is higher and the nitriding efficiency is also good.

[0095] Compared with Comparative Example 2, due to the high-temperature aging treatment of the material, the depth of the nitriding treatment layer of Example 2 is thicker than that of Comparative Example 2, that is, the nitriding efficiency of Example 2 is higher than that of Comparative Example 2. The elongation of Example 2 is much greater than that of Comparative Example 2. Although the present invention reduces the hardness of the material during high-temperature aging, the subsequent sand blasting treatment and gas nitriding treatment can effectively increase the surface hardness of Example 1 to a level similar to that of Comparative Example 1, ensuring that the material reaches the required surface hardness while maintaining good elongation.

[0096] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A gas nitriding method for an iron-nickel-chromium austenitic high elastic alloy, characterized in that: The method comprises: S1. subjecting the iron-nickel-chromium series austenitic high elastic alloy to high temperature aging treatment, wherein the temperature of the high temperature aging treatment is 750-830° C., and the holding time of the high temperature aging treatment is 3-5 hours; S2. Performing gas nitriding treatment on the alloy after high temperature aging treatment.

2. The gas nitriding method according to claim 1, characterized in that: After the step S1, a sand blasting process is also included.

3. The gas nitriding method according to claim 2, characterized in that: The sand blowing treatment is water sand blowing treatment, the raw material of the water sand blowing treatment is 50-150 mesh sand particles, the medium of the water sand blowing treatment is water, the pressure of the water sand blowing treatment is 0.2-0.4 MPa, and the coverage of the water sand blowing is 150-200%.

4. The gas nitriding method according to claim 1, characterized in that: The steps of gas nitriding treatment include: The alloy after high temperature aging treatment is loaded into a nitriding furnace and sequentially subjected to the heating stage, nitriding stage, diffusion stage and cooling stage treatments.

5. The gas nitriding method according to claim 4, characterized in that: The temperature rising step comprises: Nitrogen is introduced into the nitriding furnace, the air in the furnace is exhausted, and the temperature is raised to 500-560° C. during the introduction of ammonia; wherein the heating rate is less than or equal to 90° C. / h.

6. The gas nitriding method according to claim 4, characterized in that: The nitriding stage comprises: Ammonia is continuously introduced, the temperature of the nitriding furnace is controlled at 500-560°C, the nitriding time is 30-50 hours, the decomposition rate of ammonia is 30-50%, and the pressure in the nitriding furnace is 0.1-0.3 MPa.

7. The gas nitriding method according to claim 4, characterized in that: The diffusion section step includes: Ammonia gas is continuously introduced, the temperature of the nitriding furnace is controlled at 530-580°C, the insulation time is 1-2 hours, and the decomposition rate of ammonia gas is 60-80%.

8. The gas nitriding method according to claim 4, characterized in that: The cooling stage step comprises: Continue to introduce ammonia gas, control the temperature of the nitriding furnace to drop below 150°C, then stop introducing ammonia gas and cool the furnace; wherein the cooling rate is less than or equal to 130°C / h.

9. A gas nitrided iron-nickel-chromium austenitic high elastic alloy, characterized in that: The gas nitrided iron-nickel-chromium austenitic high elastic alloy is obtained by the gas nitriding method of the iron-nickel-chromium austenitic high elastic alloy according to any one of claims 1 to 8.

10. The gas nitrided iron-nickel-chromium austenitic high elastic alloy according to claim 9, characterized in that: The gas nitrided iron-nickel-chromium austenitic high elastic alloy has a surface hardness of more than 1050 HV, an elongation of more than 10%, and a thickness of the nitrided layer of more than 25 um.